A Creation of Comprehensive Factual Information Sheet to Prove the Right in Thai Nationality: A Case Study of Stateless Persons in Saiyok District, Kanchanaburi Province - Samlee-on, Wisarut (Huachiew Chalermprakiet Law Journal, 2024)
The objective of research is to present the guideline for the recreational cannabis use in Thailand under legal framework. According to the removal cannabis from the list of Narcotic drugs in Category 5 of new Narcotics Code, promulgated by the Ministry of Public Health and the approval of Thailand’s Narcotics Control Board, paves the way to be allowed using non-narcotic cannabis components legally. In addition, cannabis is a medicinal plant that can be used for a variety of purposes such as fiber, oil and seed for consumption, therapy and relaxation, it is result in the widespread use of cannabis and cultivation. However, the obligations of the Single Convention on Narcotics of 1961, signed by Thai Government becomes the main problem toward the recreational use of cannabis. This research aims to review the concepts on Narcotics especially legal utilization of recreational cannabis use, the principle of international Narcotics laws and the foreign laws which allow the recreational cannabis use such as The Netherlands, Australian Capital Territory, and Indonesia. The results of the study are drawn into the analysis and the suggestions the proper way to measure the recreational cannabis use in Thailand such as cannabis plants at premises within a residence or household should determine the appropriate amount of cultivation, the registration of cannabis growing should be legally enforceable to control the amount of cannabis cultivation, the determination of penalties in the Bill of Cannabis and Hemp Act B.E. ... regarding the possession of cannabis after the expiration of the registration or license expiration, as well as the sale of cannabis must be sold by a person who has received a license, permission of possession limits for cannabis, and the minimum purchase quantity of cannabis should be limited via the requiring registration of cannabis users through the Ministry of Public Health's application or website.